2016
DOI: 10.1111/wvn.12127
|View full text |Cite
|
Sign up to set email alerts
|

Nursing Practice Guidelines in China do Need Reform: A Critical Appraisal Using the AGREE II Instrument

Abstract: This research found an absence of a systematic guideline development methodology and a tendency to rely on expert opinion in the process of developing NPGs. The readers should consider these flaws and limitations when using recommendations in those NPGs.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
15
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 14 publications
(17 citation statements)
references
References 15 publications
2
15
0
Order By: Relevance
“…This obviously limits their value in guiding clinical practice and clinical decision making. The evidence implementation programs were mostly quantitative case study analysis with patient outcomes without a theoretical framework supporting the whole evidence implementation project (Jin et al, ). Generally, these EBN publications were of low quality and that may explain why many core nursing journals nowadays seldom accept EBN papers.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…This obviously limits their value in guiding clinical practice and clinical decision making. The evidence implementation programs were mostly quantitative case study analysis with patient outcomes without a theoretical framework supporting the whole evidence implementation project (Jin et al, ). Generally, these EBN publications were of low quality and that may explain why many core nursing journals nowadays seldom accept EBN papers.…”
Section: Discussionmentioning
confidence: 99%
“…One paper explored the evidence implementation domain, specifically the strategies adopted and barriers encountered in clinical evidence‐based practice (Cheng et al, ). The other paper evaluated the quality of nursing practice guidelines developed in mainland China and reported that these were predominantly of poor quality (Jin et al, ). These 5 papers all centred on single aspects of EBN, and a broad and general overview of EBN development is lacking.…”
Section: Introductionmentioning
confidence: 99%
“…From these, only 186 corresponded to publications in the last 5 years, only 112 used the AGREE II to evaluate clinical protocols, and 74 consisted in systematic reviews of protocols. Only one study referred to Nursing 15 and none addressed the development of clinical protocols in gynecology.…”
Section: Discussionmentioning
confidence: 99%
“…The methodological assessment tools for preclinical and clinical studies, systematic review and meta‐analysis, and CPGs were different, and AGREE Ⅱ instrument is recommended and suitable for developing CPGs . There are about 18 studies assessing the quality of CPGs in China using the AGREE instrument, which were published in English journals, including the fields of traditional Chinese medicine, otorhinolaryngology, hepatocellular carcinoma, myasthenia gravis, hypertension, respiratory diseases, squamous cell carcinoma of the head and neck, pancreatic cancer, nursing, lung cancer, stress ulcer prophylaxis, and integrative medicine . The first paper of the AGREE Ⅱ instrument in China was published by Zhang et al .…”
Section: Discussionmentioning
confidence: 99%